Per Capita Consumption and Growth: Comment - Bertrand, Trent J. (Quarterly Journal of Economics, 1968)
Journal Article Per Capita Consumption and Growth: Comment Get access Trent J. Bertband Trent J. Bertband Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 1, February 1968, Pages 165–167, https://doi.org/10.2307/1882251 Published: 01 February 1968